Kampanye #IBELONG UNHCR Dalam Membantu Mengakhiri Isu Statelessness di Kirgizstan - Medina Azahara (Journal of International Relations Diponegoro, 2023)
One of the fundamental rights that humans have is the right to have nationality. When someone is granted a nationality by a country, he or she has been fully recognized by that country which will automatically protect the other rights that they have. However, there are many people who still do not have a nationality, known as statelessness. In 2019, among developed and developing countries that are still experiencing difficulties to end this issue, Kyrgyzstan became the first country in the world that successfully end statelessness through a campaign issued by UNHCR, #IBELONG, in 2014. The author obtains data  through literature study such as journals, books, reports of international organizations, websites, and international news. This research is a qualitative research using the process-tracing method in conducting data analysis. By using institutionalism theory, this research argues that Kyrgyzstan’s success in ending statelessness is driven by the cooperation between the Kyrgyz government and UNHCR through #IBELONG Campaign and its supporting program where the awareness of civil society increases and then moves together in carrying out legal advocacy to stateless people in various regions of Kyrgyzstan which then had a major influence in ending the issue of statelessness.Key Words: Human Rights, Nationality, Statelessness, UNHCR, Campaign